2010
DOI: 10.1016/j.heares.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Age-related hearing loss: Is it a preventable condition?

Abstract: Numerous techniques have been tested to attempt to prevent the onset or progression of age-related hearing loss (ARHL): raising the animals in an augmented acoustic environment (used successfully in mouse and rat models), enhancing the antioxidant defenses with exogenous antioxidant treatments (used with mixed results in mouse and rat models), raising the animals with a calorie restricted diet (used successfully in mouse and rat models), restoring lost endocochlear potential voltage with exogenous electrical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 105 publications
2
88
0
3
Order By: Relevance
“…Development of age-related hearing loss (ARHL) is determined by cumulative effects of individual's genetic predisposition and deleterious auditory exposures. While it may be difficult to modify genetic predisposition, it may be theoretically possible to prevent ARHL by minimizing ototraumatic exposures during the lifespan 10 . Environmental risk factors like exposure to noise, use of ototoxic drugs, head injuries are all modifiable.…”
Section: Discussionmentioning
confidence: 99%
“…Development of age-related hearing loss (ARHL) is determined by cumulative effects of individual's genetic predisposition and deleterious auditory exposures. While it may be difficult to modify genetic predisposition, it may be theoretically possible to prevent ARHL by minimizing ototraumatic exposures during the lifespan 10 . Environmental risk factors like exposure to noise, use of ototoxic drugs, head injuries are all modifiable.…”
Section: Discussionmentioning
confidence: 99%
“…"Pure tone averages" (PTA) were derived by calculating hearing loss at each frequency, averaged across the left and right ears. Given that age-related hearing loss begins at higher frequencies and, with increasing age, expands in both magnitude and extent, we separately explored the effects of hearing loss at these three frequencies (Bielefeld, Tanaka, Chen, & Henderson, 2010). To approximate verbal IQ, predicted verbal IQ was derived from the National Adult Reading Test (NART) (Nelson, 1982).…”
Section: Background Assessmentsmentioning
confidence: 99%
“…In experimental models, hearing levels were evaluated in antioxidant therapy given as combination in hearing loss emerging with age, and improvement in hearing levels was proven with the BERA test [29]. In tests performed on humans following experimental studies, age-related hearing loss was shown to be prevented with diet and antioxidants [30]. In our study, PON1 and ARE values were found to be lower in metabolic presbycusis patients, compared to the control group.…”
Section: Discussionmentioning
confidence: 65%